2020
DOI: 10.1029/2020jd033644
|View full text |Cite
|
Sign up to set email alerts
|

Long‐Term Variability and Tendencies in Migrating Diurnal Tide From WACCM6 Simulations During 1850–2014

Abstract: Long-term variability and tendencies in migrating diurnal tide (DW1) are investigated for the first time using a three-member ensemble of historical simulations by NCAR's Whole Atmosphere Community Climate Model, latest Version 6 (WACCM6) for 1850-2014 (165 years). The model reproduces the climatological features of the tide in temperature (T), zonal wind (U), and meridional wind (V). The amplitudes peak in the upper mesosphere and lower thermosphere (above~0.001 hPa) at the equator for T (~10 K) and over 20-3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 41 publications
1
8
0
Order By: Relevance
“…(2017) and Ramesh et al. (2020), we begin with the tidal anomaly. This is defined as the deviation of each month from the climatological mean.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…(2017) and Ramesh et al. (2020), we begin with the tidal anomaly. This is defined as the deviation of each month from the climatological mean.…”
Section: Methodsmentioning
confidence: 99%
“…We will now explain our linear regression analysis of the 12-hr tidal amplitudes. Similarly to Gan et al (2017) and Ramesh et al (2020), we begin with the tidal anomaly. This is defined as the deviation of each month from the climatological mean.…”
Section: Linear Regressionmentioning
confidence: 99%
“…Then, the winter (DJF) mean of the DW1 anomalies is calculated. Natural forcing, such as the solar cycle (represented by F107), QBO, ENSO, and long-term trends, jointly affect the DW1 tidal amplitude (e.g., Dhadly et al, 2018;Gurubaran et al, 2005;Gurubaran & Rajaram, 1999;Lieberman et al, 2007;Liu et al, 2017;Pedatella & Liu, 2012;Sridharan, 2019Sridharan, , 2020Sridharan et al, 2010;Vincent et al, 1998;Xu et al, 2009). To isolate the linear forcing of ENSO from the interference of other factors, a multivariate linear regression (MLR) analysis is applied on the anomalous time series at each latitude and altitude, the same as that used in Li et al (2013).…”
Section: Methodsmentioning
confidence: 99%
“…As suggested by the WACCM version 6 simulations with self-generated QBO and ENSO, there is a positive response of the MLT DW1 tide to El Niño during the winter (Ramesh et al, 2020). However, Liu et al (2017) found that DW1 amplitudes are suppressed during the winters of El Niño events based on simulations of the ground-to-topside atmosphere-ionosphere for aeronomy (GAIA) model.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation